Risk factors and services to reduce child sexual abuse recurrence - Palusci, Vincent J. (Child maltreatment, 2020)
Child sexual abuse (CSA) is associated with a range of negative consequences for victims that are compounded when it recurs. We used the National Child Abuse and Neglect Data System to study a cohort of 42,036 children in 45 U.S. states with sexual abuse reports first confirmed by child protective services (CPS) during 2010 in order to identify children with increased risk for recurrence. A small proportion (3.6%) had a second confirmed sexual abuse report through 2015. In multivariate models, female gender, family hearing and vision problems, other child maltreatment, and other family violence were associated with increased risk of recurrence, while younger children, Hispanic families, and those with substance abuse tended to have less risk. One fourth of recurrence involved the same offender, usually a parent or caretaker. One fourth of cases were referred for any CPS services, which were more likely to be provided for families with poverty, drug or alcohol problems, or other violence. Only substance abuse services significantly reduced recurrence in multivariable models. Those trying to reduce CSA recurrence should recognize that certain case characteristics are associated with greater recurrence, and most CPS services do not significantly reduce CSA recurrence.